Spesiasi Senyawa Organotimah dengan Teknik Kromatografi Pasangan Ion-Fasa Terbalik - Aman Sentosa Panggabean; Muhammad Bachri Amran; Buchari Buchari; Sadijah Achmad (Institut Teknologi Bandung, 2007)
The application of Ion Pair-Reversed Phase chromatography (IP-RP) technique for speciation of dibutyltin (DBT),tributyltin (TBT) and triphenyltin (TPhT) species has been studied. All of the species were able to separate on an ionpair-reversed phase chromatographic column. The eluats were detected online by the use of Hydride Generation-QuartzFurnace Atomic Absorption Spectrophotometry (HG-QFAAS) method. The eluent consisted of a mixture of methanol :water : acetic acid with a composition of 80:19:1, containing 1 mM of decane sulfonate as ion pairing reagent. The pHof the eluent was adjusted with 1 M H2SO4. The separation of all the species at the above conditions was good, whichwas shown by the values of the fundamental chromatographic parameters. The capacity factor (k) for DBT, TBT andTPhT species were 0.27, 2.54 and 5.92 respectively. The resolution (Rs) values for DBT-TBT and TBT-TPhT separationwere 2.92 and 2.42 respectively, while the selectivity for DBT-TBT and TBT-TPhT were 9.76 and 3.50, respectively.These data show the effectiveness of the developed chromatographic system.